Sintesis Metil Ester Asam Lemak dari Biji Alpukat (Parsea americana Mill) Menggunakan Polimer Penyangga Katalis Berbahan Dasar Eugenol: Synthesis of Fatty Acid Methyl Ester from Avocado Seeds (Parsea americana Mill) using Polymer Support Catalyst Based on Eugenol - Sumarni; Erwin Abdul Rahim; Ni Ketut Sumarni; Ruslan; Hardi Ys.; Moh. Mirzan (KOVALEN: Jurnal Riset Kimia, 2020)
Research on the manufacture of methyl esters from avocado seeds (Parsea americana Mill) with eugenol-based catalysts has been conducted. The aim is to determine the catalyst concentration used to produce methyl esters with the highest rendement and determine the composition of fatty acid methyl ester in avocado seeds. This study was used variations in concentrations of 0.25%, 1%, 1.75%, 2.25%, and 3%. The results of this study showed that the best concentration is 2.25% with the calculation of the results of 24.8% methyl esters in avocado seeds, namely lignoceric and octadecenoic acid methyl ester. Keywords: Avocado seeds, fatty acid methyl esters